Second Generation in Czech Family Businesses and their impact on Business Model Innovations - Prokop, Jan; Jurek, Martin; Kubíček, Aleš; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2022)
This thesis analyses Business Model Innovations within selected family businesses in the Czech Republic. The main goal is to find common patterns regarding Business Model Innovations from the viewpoint of the second generation. The research also observes the diversification strategies used by the second generation. Business model innovations are mapped on a graphical tool, the Business Model Canvas. The research method is qualitative primary research via in-depth interviews with selected second-generation members of 15 Czech family businesses. The research summary is synthesized from two perspectives based on the findings from the interviews. The research summary provides the reader with a clear understanding of how the second generation of Czech family businesses innovates their business model regardless of the company’s size or background.
Vedoucí práce: Martin Jurek
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses